Neighborhood Food Infrastructure and Food Security in Metropolitan Detroit. Issue 3 (27th August 2017) - Allard, Scott W.; Wathen, Maria V.; Shaefer, H. Luke; Danziger, Sandra K.
Abstract : Concern about spatial access to food retailers and its relationship to household food security has increased in recent years, placing greater importance on understanding how proximity to food retailers is related to household food consumption. Using data from the Michigan Recession and Recovery Study (MRRS), a panel survey of working‐age adults in the Detroit Metropolitan Area, this article explores whether access to the food retailers is associated with food insecurity. We use unique data about food retailers in metropolitan Detroit to develop an array of food retailer access measures that account for distance to nearest retailer, density of retailers, commute times, mode of transit, and type of retailer. Across most measures, we find that many vulnerable population groups have greater or at least comparable spatial access to food resources as less vulnerable populations groups. There is little evidence, however, that greater access to food retailers is associated with food security.